The Potential of Subak Uma Lambing in Sibangkaja Abiansemal Village, Badung Based on Organic Farming Culture as Ectourism - I Wayan Wesna Astara; I Wayan Budiarta; Kadek Merta Wijaya; I Gusti Agus Maha Putra Sanjaya; Tanjung Subrata; Desak Ketut Tristiana Sukmadewi; Naori Miyazawa (Journal of Legal and Cultural Analytics, 2023)
Partners in this service are Prajuru Subak Umalambing, which involves organic and non-organic farmers in Subak Umalambing Sibangkaja Ecotourism. The partner's problems are the developed Subak Lambing ecotourism has not been able to implement state law and local law (adat law, awig-awig, and perarem) as part of legal certainty. Objectives: First, to provide legal awareness of ecotourism and organic farming-based culture with the expectation that the law has a cultural meaning in managing ecotourism; second, the potential of Subak Umalambing as ecotourism organic farming requires synergy between Kelian Subak and the Astungkara Way Foundation in managing small tradition-based agriculture (farmers) that can provide added value to farmers. Third, Subak Umalambing Ecotourism in a "redesign" manner and public health needs continuous education and state intervention, especially village government Sibangkaja, to design sustainable ecotourism with the protection of state law